2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1600.r1
|View full text |Cite
|
Sign up to set email alerts
|

No difference in long-term micromotion between fully cemented and hybrid fixation in revision total knee arthroplasty: a randomized controlled trial

Abstract: Aims Both the femoral and tibial component are usually cemented at revision total knee arthroplasty (rTKA), while stems can be added with either cemented or press-fit (hybrid) fixation. The aim of this study was to compare the long-term stability of rTKA with cemented and press-fitted stems, using radiostereometric analysis (RSA). Methods This is a follow-up of a randomized controlled trial, initially involving 32 patients, of whom 19 (nine cemented, ten hybrid) were available for follow-up ten years postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Although a significant number of implants showed continuous migration or a high degree of micromotion (> 1 mm or > 1°), longer follow-up RSA in revision knee surgery with condylar implants did not show signs of aseptic loosening for this potential group at risk ( 4 , 6 ). In addition, a retrospective analysis of a fully cemented Legion HK cohort showed only 1 femoral component loosening in 147 cases with a mean follow-up of 3.8 years ( 16 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although a significant number of implants showed continuous migration or a high degree of micromotion (> 1 mm or > 1°), longer follow-up RSA in revision knee surgery with condylar implants did not show signs of aseptic loosening for this potential group at risk ( 4 , 6 ). In addition, a retrospective analysis of a fully cemented Legion HK cohort showed only 1 femoral component loosening in 147 cases with a mean follow-up of 3.8 years ( 16 ).…”
Section: Discussionmentioning
confidence: 86%
“…The degree of micromotion assessed by RSA in the first 2 years after surgery is associated with late revision for aseptic loosening in primary total knee arthroplasty (TKA) ( 2 , 3 ). From the sparse data available on condylar revision knee implants, it can be observed that higher degrees of micromotion do not result in later aseptic loosening ( 4 - 6 ).…”
mentioning
confidence: 99%
“…Given the increased level of constraint, higher forces are transmitted to the bone-implant interface, so to prevent micromotion and implant loosening, stemmed implants are utilized to enhance fixation and participate in load-sharing. Stems may be press-fit or cemented per surgeon preference, taking into account specific patient factors including bone quality and pre-existing femoral deformity 16 .…”
Section: Implant Selectionmentioning
confidence: 99%
“…To enlarge the area of the osseous interface and decrease forces on weakened bone, components with stems are often used, and these can be fully cemented or press-fit. Mills et al 60 , using radiostereometric analysis, compared the long-term stability of revision total knee replacements with either fully cemented or press-fitted stems (hybrid fixation). Their findings showed good long-term fixation with no difference in micromotion and PROMs (at the 10-year follow-up) between fully cemented and hybrid fixation of stems in patients with Anderson Orthopaedic Research Institute type-I or II bone defects.…”
Section: Revision Tka Implant Design and Surgical Techniquementioning
confidence: 99%